“LEARN”, a novel teaching method for Chinese clinical clerkship: A cross-sectional study - Chen, Xiangyu; Gong, Matthew F.; Wu, Song; He, Jinshen (Frontiers in Surgery, 2023)
Background Despite the clerkship being crucial in the training of a future doctor, no widely accepted education model has been proposed. This study devised a new model for clinical clerkship rotations, titled “LEARN” for Lecture, English-video, Advisor, Real-case and Notion, and evaluated whether the LEARN model is appropriate for medical education in China. Methods A cross-sectional study was performed among 101 fourth-year students from the Xiangya School of Medicine during an Orthopaedic Surgery clerkship rotation in the Third Xiangya Hospital. They were divided into seven groups and took clerkship based on the LEARN model. A questionnaire was collected at the conclusion to measure learning outcomes. Results The LEARN model was highly accepted with the acceptance of five sessions being 95.92% (94/98), 93.88% (92/98), 96.98% (97/98), 100% (98/98) and 96.94% (95/98). The outcomes of two genders were comparable, whereas a difference was observed in the test score among groups (group 3 scored 93.93±5.20, higher than others). Quantitative analysis showed that positive correlations existed in participation in the Notion (Notion means students’ case discussion) section with leadership (r=0.84, 95% CI: 0.72-0.94, p<0.001), participation in the Real-case section with leadership (r=0.66, 95% CI: 0.50-0.80, p<0.001), participation in the Real-case section with mastery of inquiring skills (r=0.57, 95% CI: 0.40-0.71, p<0.001) and participation in the Notion section with mastery of physical examination skills (r=0.56, 95% CI: 0.40-0.69, p<0.001). Further qualitative analysis demonstrated that high-level participation in the English-video section indicated better outcomes in mastery of inquiring (p<0.01), physical examination (p<0.001), film reading (p<0.01) and clinical reasoning (p<0.01) skills. Conclusions Our results support the LEARN model is a promising method for medical clerkship in China. Further research involving more participants and more meticulous design is planned to test its efficacy. For refinement, educators may try to promote students’ participation in the English-video session.